Pengaruh Perilaku Belajar, Gaya Mengajar Dosen, dan Kecerdasan Emosional Terhadap Pemahaman Mahasiswa pada Mata Kuliah Pengantar Akuntansi - Veri Rahardian; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research is an associative study to analyze the relationship or relationship or correlation between Learning Behavior, Lecturer Teaching Style, and Emotional Intelligence on Students Understanding of Introductory Accounting Courses. The population in this study is students of the Islamic University of Malang in Accounting study program from 2019 to 2020. The sampling technique used in this study was simple random sampling. The results showed that learning behavior had a positive and significant effect on students understanding of introductory accounting courses. The higher the level of learning behavior, the more it affects student understanding. The teaching style of the lecturer has a positive and significant effect on students' understanding of the introductory accounting course. The higher the level of the lecturer's teaching style, the more it affects student understanding. Emotional intelligence has a positive and significant effect on students' understanding of introductory accounting courses. The higher the level of emotional intelligence, the more it affects student understanding. The coefficient of determination R² which shows 0.532, it means that 53.20% student understanding is influenced by learning behavior, lecturer teaching style, and emotional intelligence, while the remaining 46.80% student understanding is influenced by other variables not examined in this study.Keywords: Learning behavior, lecturer teaching style, emotional intelligence, accounting courses